2016
DOI: 10.1155/2016/9624974
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Crushed Red-Bed Soft Rock Mixtures Used in Subgrade

Abstract: Slaking red-bed soft rocks are widely distributed in the south of Anhui Province, China, and several highways will go through this area. It is important to evaluate their physical and mechanical characteristics for the purpose of using this kind of soft rocks as materials for road construction. In this paper, the compacting tests, the resilient modulus tests, the California bearing ratio (CBR) tests, and permeability tests have been carried out on crushed red-bed soft rock mixtures. The test results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…This study mainly focuses on the influence of mineral compositions on geomorphic characteristics, particularly the layered structure and color of red beds. The mineral compositions of red beds (1,536 groups data) were collected from the previous studies as shown in Supplementary Table 1 (e.g., (Bai et al 2020;Chen et al 2014;Jian et al 2009;Li et al 2023;Li et al 2015;Li et al 2013;Liu et al 2020;Marat et al 2022;Wang et al 2018;Wang et al 2014;Wang et al 2017;Yao et al 2016;Zha et al 2022;Zhang et al 2016;Zhang et al 2020;Zhang et al 2021)). These studies used semi quantitative or quantitative methods in XRD technology to statistically analyze the differences in mineral composition between different red beds (e.g., quartz, feldspar, mica, hematite, clay minerals, and calcite), as detailed in the aforementioned literatures.…”
Section: Data Collectionmentioning
confidence: 99%
“…This study mainly focuses on the influence of mineral compositions on geomorphic characteristics, particularly the layered structure and color of red beds. The mineral compositions of red beds (1,536 groups data) were collected from the previous studies as shown in Supplementary Table 1 (e.g., (Bai et al 2020;Chen et al 2014;Jian et al 2009;Li et al 2023;Li et al 2015;Li et al 2013;Liu et al 2020;Marat et al 2022;Wang et al 2018;Wang et al 2014;Wang et al 2017;Yao et al 2016;Zha et al 2022;Zhang et al 2016;Zhang et al 2020;Zhang et al 2021)). These studies used semi quantitative or quantitative methods in XRD technology to statistically analyze the differences in mineral composition between different red beds (e.g., quartz, feldspar, mica, hematite, clay minerals, and calcite), as detailed in the aforementioned literatures.…”
Section: Data Collectionmentioning
confidence: 99%
“…e disintegration of soft rock is a physical phenomenon with complex mechanism. In order to reveal this mechanism, some researchers have carried out tests on rock disintegration to characterize the variation law of the disintegration process under the macroscopic conditions such as the number of cycles, the hydraulic properties, and the mass of disintegration residues [3,4]. At the same time, X-ray diffraction, mercury injection test, and CT scanning were used to study the material composition, fracture propagation degree, and void ratio of soft rock to explain the internal factors of disintegration [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on sedimentary rocks used in highway engineering mainly focuses on the performance of red sandstone, and its uniaxial compressive strength and indirect tensile strength are superior to white sandstone and yellow sandstone [15]. Yao et al [16] evaluated the physical and mechanical properties of red sandstone distributed in southern Anhui, with the aim of using this soft rock as a road construction material. The results demonstrated that the mixture consisting of sandstone can be directly applied into highway construction after particular preliminary steps are performed.…”
Section: Introductionmentioning
confidence: 99%